Antifungal oxoaporphine alkaloids - Sharma, Alpana S. 1953-
An economic synthesis of liriodenine, an oxoaporphine alkaloid, which has shown significant antifungal activity, has been accomplished. The synthetic procedure utilized is basically the same as reported in the literature with certain modifications in order to obtain inexpensive starting materials and high yielding reactions. One of the starting material, o-nitrophenyl acetic was prepared by following a literature procedure utilizing o-nitrotoluene and ethyloxalate. The oxidation of l-benzylisoquinoline was accomplished in 59% yield by utilizing potassium dichromate and 70% acetic acid. The Pschorr cydization of 1-2'-aminobenzoylisoquinolines to liriodenine was accomplished in 51% yield. The over-all yield was 10.04% The cost of the synthesis of liriodenine was reduced from $1800/kg to $795/kg. Oxoaporphine alkaloids oxoglaucine, corunnine, O,N-dimethylliriodendronine, liriodenine, lysicamine and oxonantenine were obtained and tested against B. subtilis, staph. aureus, M. smegmatis, A. niger, S. cerevisiae and C. albicans. The results indicate that the presence of a methylenediory group in the ring A is essential for an oxoaporphine alkaloid to show significant antifungal activity
Available to the general public.
Thesis (MS Pharmacognosy)--University of Mississippi, December 1977.
Keywords: Antifungal agents; Alkaloids